The Global Village : a case study of the frescoes at Akrotiri as evidence for multiculturalism in the Bronze Age Aegean - Van den Brink, Jessica Hendrika (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.